Antioxidant Activity of Theobroma cacao L. Husk Ethyl Acetate Fraction in Peel-Off Mask Formulation Measured by the DPPH Assay - Rizki, Risnanda Farzia; Aisya, Mauly Rahadatul; Khairan, Khairan (Malacca Pharmaceutics, 2025)
Cocoa fruit (Theobroma cacao) is one of Indonesia's most important commodities and is widely used as a raw material in various industries. Until now, cocoa fruit has primarily been used for its seeds, while its skin has not been widely explored. This study aims to formulate a peel-off mask from cacao husk and determine its antioxidant activity. The antioxidant test method used was the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Analysis results showed that the ethyl acetate fraction contained secondary metabolites, including flavonoids, tannins, and steroids. However, the peel-off mask formulation made with a combination of the ethyl acetate fraction of cocoa husk and polyvinyl alcohol was unstable due to changes in its characteristics during storage. Nevertheless, the resulting peel-off mask exhibited relatively strong antioxidant activity, with IC₅₀ values of 6.819 ppm for the ethyl acetate fraction and 11.596 ppm for the mask. These results suggest that cocoa husk contains bioactive compounds that support strong antioxidant activity. Therefore, cocoa husk has great potential as an active ingredient in cosmetic formulations. However, further formula optimization is needed to improve the formulation's stability while maintaining optimal antioxidant activity.